Pembangunan Ekonomi Berkelanjutan: Pendekatan Studi Ekonomi Ibn Khaldun - Noviendri Djalil (Liquidity, 2026)
The need for a more holistic and ethical development paradigm has intensified as a result of the global crisis characterized by economic inequality, environmental degradation, and the dominance of a materialistic development paradigm. The purpose of this study is to examine Ibn Khaldun's economic theory and re-integrate it into the context of sustainable economic development. This study analyzes Ibn Khaldun's major work, the Muqaddimah, and compares it with the principles of sustainable development found in the Sustainable Development Goals (SDGs). This study uses a qualitative approach and library research methods. The study shows that Ibn Khaldun's ideas, particularly the concept of umran (civilization), fiscal justice, work ethics, and the proportional role of the state, align with the pillars of sustainable development that emphasize the balance between economic growth, social welfare, and system sustainability. Ibn Khaldun also placed moral values as the foundation of a standard for development focused on economic growth and long-term well-being. According to this study, Ibn Khaldun's ideas should be incorporated into a modern Islamic economic framework and utilized in public policymaking focused on multidimensional sustainability.